Impact of Cardiovascular Risk Factors in Adolescence, Young Adulthood, and Midlife on Late-Life Cognition: Study of Healthy Aging in African Americans. (18th May 2021) - George, Kristen M; Gilsanz, Paola; Peterson, Rachel L; Barnes, Lisa L; DeCarli, Charles S; Mayeda, Elizabeth Rose; Mungas, Dan M; Whitmer, Rachel A
Abstract: Background: Midlife cardiovascular risk factors (CVRFs) increase risk of dementia. Black Americans experience an elevated prevalence of CVRFs and dementia. However, little is known of how CVRFs prior to midlife affect late-life cognition. We examined CVRFs in adolescence, young adulthood, and midlife with late-life cognition in the Study of Healthy Aging in African Americans (STAR). Method: STAR assesses cognitive aging among 764 Black Americans aged ≥50 (mean age = 69; SD = 9; range = 53–95). Participants' body mass index, blood pressure, glucose, and total cholesterol were collected during Multiphasic Health Checkups (MHC; 1964–1985). At STAR baseline (2018–2019), executive function, verbal episodic memory, and semantic memory were measured using the Spanish and English Neuropsychological Assessment Scales. Linear regression models examined associations between CVRFs and cognition adjusting for demographics and years since MHC. Results: At MHC, 36% of participants had 1 CVRF and 26% had ≥2. Twenty-two percent of participants were adolescents (age 12–20), 62% young adults (age 21–34), and 16% midlife adults (age 35–56). Overweight/obesity was not associated with cognition. Hypertension was associated with worse executive function (β [95% CI]: −0.14 [−0.28, −0.0003]) and verbal episodic memory (β [95% CI]: −0.22 [−0.37, −0.07]) compared to normotension. Diabetes was associated with worse executive function (β [95% CI]: −0.43 [−0.83, −0.03]). Having ≥2 CVRFs (vs 0) was associated with worse executive function (β [95% CI]: −0.19 [−0.34, −0.03]) and verbal episodic memory (β [95% CI]: −0.25 [−0.41, −0.08]). Adolescents with hypertension had lower late-life executive function compared to normotensive adolescents (β [95% CI]: −0.39 [−0.67, −0.11]). Young adulthood hypertension (β [95% CI]: −0.29 [−0.49, −0.09]) and midlife hyperlipidemia (β [95% CI]: −0.386 [−0.70, −0.02]) were associated with lower verbal episodic memory. Conclusions: Among Black Americans, life-course CVRFs were associated with poorer executive function and verbal episodic memory emphasizing the importance of cardiovascular health on the aging brain.